LET THEM TEACH: PENGARUH MODEL PEMBELAJARAN PROBLEM POSING TIPE POST SOLUTION POSING DENGAN METODE BUZZ GROUP TERHADAP HASIL BELAJAR FISIKA SISWA - Lailiya AR, Huri; Gustina, Gustina (Universitas Tadulako, 2021)
This study aims to determine whether there was an effect of the Post Solution Posing Problem Posing learning model with the Buzz Group method on student learning outcomes. This research was a quasi-experimental design with an equivalent pretest-posttest group design. The population of this study were all students of class XI SMA Negeri 1 Sigi. The sampling technique used in this study was purposive sampling with a sample of 28 students in class XI MIPA 1 as the experimental group and class XI MIPA 3 with 28 students as a control group. The instrument for learning physics was a multiple-choice test that has been validated. The test of physics learning outcomes obtained showed the average value of the experimental group was 14.79 with a standard deviation of 2.32. Meanwhile in the control class obtained an average value of 12.50 with a standard deviation of 2.54. The t-test hypothesis test (two parties) was obtained tcount = 3.45 and ttable = 2.00 at the real level = 0.05. It shows that tcount was outside the H0 acceptance area. So it can be concluded that there was an effect of the Post Solution Posing Problem Posing learning model with the Buzz Group method on student learning outcomes.